The Implementation of Learning Strategies to Improve Students’ Learning Outcomes at MI Bustanul Ulum Sumbersuk - Puspita, Mega; Sholikhudin, Muhammad Anang (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the effectiveness of implementing varied and structured learning strategies in improving student learning outcomes at MI Bustanul Ulum Sumbersuko. Using a qualitative approach, data were collected through observation, interviews, and document analysis. The results showed that the implementation of active learning methods, group discussions, and the use of visual media significantly increased students' active participation, learning motivation, and understanding of the material. In addition, the analysis of student needs allows for the adjustment of materials according to their abilities and background of understanding, which has a positive impact on increasing evaluation scores and critical thinking skills. This study provides recommendations for the development of sustainable learning strategies to improve the quality of education in madrasah.